Impact of Laparoscopic Resection for Colorectal Cancer on Operative Outcomes and Survival - Law, Wai Lun (2007)
OBJECTIVE: This study aimed to compare the outcomes of patients who underwent laparoscopic and open resections for colorectal cancer. Comparison of colectomy in 2 consecutive periods (period 1: January 1996–May 2000; period 2: June 2000–December 2004), with laparoscopic surgery being a surgical option in period 2, was also performed. SUMMARY BACKGROUND DATA: Prospective data of 1134 patients (448 in period 1; 656 in period 2) who underwent elective resection for colon and upper rectal cancer (above 12 cm from anal verge) were analyzed. METHODS: The operative outcome and survival were compared between patients who underwent laparoscopic and open resection in period 2. The outcomes of colorectal resections in the 2 periods were also compared. RESULTS: During period 2, the operative mortality rates of patients with laparoscopic (n = 401) and open resection (n = 255) were 0.8% and 3.7%, respectively (P = 0.022), and the morbidity rates were 21.7% and 15.7%, respectively (P = 0.068). The patients who underwent laparoscopic resection had significantly earlier return of bowel function, earlier resumption of diet, and shorter hospital stay. The 3-year overall survivals in those with nondisseminated disease were 74.4% and 78.8% for open and laparoscopic resection, respectively (P = 0.046). The operative morality rates were 4.4% and 2.6% in period 1 and period 2, respectively (P = 0.132). The 3-year overall survivals for patients with nondisseminated disease were 69.7% and 76.1% for period 1 and period 2, respectively (P = 0.019). The overall survivals in patients who underwent open resection in the 2 periods were similar (P = 0.284). CONCLUSIONS: The short-term favorable outcome of laparoscopic resection for colorectal cancer was confirmed and improvement of survival was observed with the practice of laparoscopic resection.